2014
DOI: 10.1002/ceat.201300597
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Continuous Chromatography and Racemization Processes for the Production of Pure Enantiomers

Abstract: Combining an enantioseparation by continuous chromatography with the racemization of the undesired enantiomer in a recycle is a promising approach. Two different cases were considered: limited conversion of the reaction with moderate product purity requirements and high conversion with high product purity requirements. For the first case, a simple plantwide control strategy is presented, manipulating the solvent removal in front of the racemization reactor. It is shown that the various disturbances can be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In this work the experimental implementation of an integrated process for the production of single amino acid enantiomers from a racemate, employing continuous chromatography and biocatalysis, is presented for the first time. We demonstrate that this process can be operated in stable fashion for at least over 30 h despite i) highly non-linear adsorption isotherms, ii) the existence of a memory effect in the adsorption behavior of the CSP, and iii) the lack of sophisticated online control mechanisms that have been proposed for similar process combinations previously (Amanullah and Mazzotti, 2006;Swernath et al, 2014). The experimental proof of concept run was designed employing the traditional complete separation criterion for the SMB, meaning that both outlet purities should be nearly absolute.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this work the experimental implementation of an integrated process for the production of single amino acid enantiomers from a racemate, employing continuous chromatography and biocatalysis, is presented for the first time. We demonstrate that this process can be operated in stable fashion for at least over 30 h despite i) highly non-linear adsorption isotherms, ii) the existence of a memory effect in the adsorption behavior of the CSP, and iii) the lack of sophisticated online control mechanisms that have been proposed for similar process combinations previously (Amanullah and Mazzotti, 2006;Swernath et al, 2014). The experimental proof of concept run was designed employing the traditional complete separation criterion for the SMB, meaning that both outlet purities should be nearly absolute.…”
Section: Resultsmentioning
confidence: 92%
“…In consequence, the SMB is challenged with a dynamic change in feed concentration which might require adaptation of SMB operating points during operation in order to ensure constant product purity. A recent work shows that product purities in a similar integrated process can be controlled by adjusting the retentate flow rate (Swernath et al, 2014): a similar approach can be envisioned for the integrated process concept presented in this work by reducing the feed flow rate.…”
Section: Role Of Enzyme Requirementmentioning
confidence: 92%
“…For example, it has been recently demonstrated that robustness of hybrid process concepts where SMB chromatography is coupled with crystallization and solvent removal [9] or chemical reaction and solvent removal [17] can be improved by manipulating the solvent removal rate. There is thus an obvious need to understand how different operating parameters of coupled units interact with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Many potential chromatography-based hybrid concepts have been proposed such as coupling of chromatography with crystallization [1][2][3][4][5][6][7][8][9], chemical reactions [10][11][12][13][14][15][16][17], partial solvent removal [18][19][20][21][22], or combinations of them [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The process configurations investigated had different degrees of integration and complexity. Coupled systems were studied theoretically (von Langermann et al 2012;Nimmig and Kaspereit 2013;Swernath et al 2014) and were implemented experimentally for the production of D-Psicose (Wagner et al 2011). Additionally, a combination of chromatographic SMB separation and enzymatic racemization was used by Fuereder et al (2016) for the production of pure methionine enantiomers.…”
Section: Introductionmentioning
confidence: 99%